An Analysis of Symbolism in the Five Selected Love Poems of Nicholas Gordon - Masagus Sulaiman (Alsuna: Journal of Arabic and English Language, 2019)
This research is aimed at figuring out the dominant symbolisms and the meanings in the five selected love poems of Nicholas Gordon. The descriptive-qualitative method was applied in this research. To analyze the data, the researcher used qualitative data analysis. The results showed that there were twenty five conventional symbolisms and nineteen natural symbolisms in the five selected love poems of Nicholas Gordon. In other words, four conventional symbolisms and four natural symbolisms in the first selected love poem, four conventional symbolisms and eight natural symbolisms in the second selected love poem, ten conventional symbolisms and one natural symbolism in the third selected love poem, four conventional symbolisms and three natural symbolisms in the fourth selected love poem, and three conventional symbolisms and three natural symbolisms in the fifth selected love poem. In conclusion, conventional symbolism was more dominant than natural symbolism, and most of the meanings of the poems related to feelings of happiness and sadness in line with love relationship.